A Relationship between Natural Disaster and Poverty - Awasthi, P.R. (Journal of APF Command and Staff College, 2019)
This paper aims to discuss the impact of a disaster on the lives and livelihood and how it contributes to poverty. For this purpose, two major disasters in recent history were taken as reference. The common approach in defining and measuring poverty is the monetary approach; often disaster has seen only a matter of humanitarian importance. Nepal as a prone to different kinds of natural disasters has a significant impact on lives and livelihood as well. Despite this fact, poverty is narrowly defined. As there is a significant linkage between disaster risk and poverty, the poverty-related discussions must incorporate the impact and risk of disaster while formulating poverty reduction related policies.